1987
DOI: 10.1007/bf00378935
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the responses of two Plantago species to nitrate availability in culture experiments with exponential nutrient addition

Abstract: Juvenile plants of Plantago lanceolata and P. major ssp. major were grown on nutrient solution at optimal availability of nitrate as well as at various degrees of suboptimal nitrate availability. In the optimal treatment the nutrient solution contained 7.5 mmol NO per 1. In the various suboptimal treatments nitrate of the basic solution was replaced by sulphate, and nitrate was continually added during the experimental period. The rate of addition was exponential, according to the formula: [Formula: see text] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…Due to the absence of mineral nitrogen in the pots with plants, it was concluded that the system was ammonium limited over the whole period. This is confirmed by the fact that the maximum relative growth rate of P. lanceolata is 1.85 per week (Freijsen and Otten, 1987;Kuiper and Bos, 1992), whereas an exponentially increasing ammonium addition rate of 1.37 per week was applied in the present pot experiment. One possible explanation is that the inhibition of the nitrification process is due to alMochemicals originating from the roots of P. lanceolata.…”
Section: Discussionsupporting
confidence: 67%
“…Due to the absence of mineral nitrogen in the pots with plants, it was concluded that the system was ammonium limited over the whole period. This is confirmed by the fact that the maximum relative growth rate of P. lanceolata is 1.85 per week (Freijsen and Otten, 1987;Kuiper and Bos, 1992), whereas an exponentially increasing ammonium addition rate of 1.37 per week was applied in the present pot experiment. One possible explanation is that the inhibition of the nitrification process is due to alMochemicals originating from the roots of P. lanceolata.…”
Section: Discussionsupporting
confidence: 67%
“…NUE of -N plants was strongly increased as compared to + N plants in both species. The increase was stronger in P. major than in P. lanceolata, in agreement with results of Freijsen and Otten (1988) on the same species.…”
Section: Nitrogen Depletion In Plantago 203supporting
confidence: 92%
“…A number of authors have shown that plants adjust their RGR to match suboptimum relative rates of nutrient supply (RAR) if nutrients are added at frequent intervals during the growth period (Ericsson, 1981;Ericsson and Ingestad, 1988;Freijsen and Otten, 1987;Ingestad, 1981;Ingestad and Lund, 1979;Jia and Ingestad, 1984). Thus, Equation 2 can be rewritten with RAR as the control variable:…”
Section: Theorymentioning
confidence: 99%
“…Thus, the state of the art in solution culture is the low volume, well-stirred system with frequent replenishment of nutrients using a constant RAR (Freijsen and Otten, 1987;Ingestad and Lund. 1986).…”
Section: Introductionmentioning
confidence: 99%